2012
DOI: 10.1177/147323001204000316
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Components of the Urokinase-Type Plasminogen Activator System are Related to Chronic Obstructive Pulmonary Disease Parenchymal Destruction and Airway Remodelling

Abstract: OBJECTIVE: Retrospective study to investigate levels of components of the urokinase-type plasminogen activator (uPA) system in patients with chronic obstructive pulmonary disease (COPD). METHODS: Peripheral lung tissue was obtained from patients who underwent surgical resection for benign lung diseases: 16 patients with COPD, 10 controls without lung function impairment who were smokers, and 10 controls without lung function impairment who were nonsmokers.Immunohisto chemical staining for uPA, uPA receptor (uP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 43 publications
2
27
0
Order By: Relevance
“…The relationship between uPA expression in the epithelium and small airway remodeling requires further investigation, but relating epithelial histology to uPA expression in a crosssectional study would be difficult to interpret. Our previous studies found that uPA staining increased in the small airway 15 This study is the first to investigate the uPA protein expression ex vivo in the small airways of a number of control and COPD individuals. These findings provide a basis for further investigation of the role of uPA in the epithelium.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The relationship between uPA expression in the epithelium and small airway remodeling requires further investigation, but relating epithelial histology to uPA expression in a crosssectional study would be difficult to interpret. Our previous studies found that uPA staining increased in the small airway 15 This study is the first to investigate the uPA protein expression ex vivo in the small airways of a number of control and COPD individuals. These findings provide a basis for further investigation of the role of uPA in the epithelium.…”
Section: Discussionmentioning
confidence: 77%
“…The elevated levels of uPAR in small airway epithelia and alveolar wall cells were also observed in COPD patients with a significant emphysema in our previous study. 15 Lungs from uPAR( À / À ) mice displayed nonspecific interstitial pneumonia-like pathological features, with a significant increase in alveolar septal width and collagen content. 36 These studies suggest that downregulation of uPAR may be related with interstitial pulmonary fibrosis; however, the uPAR-initiated EMT in small airway of COPD patients may be accounting for small airway fibrosis in COPD.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…suPAR can convert plasminogen to plasmin, which degrades fibrin, activates matrix metalloproteases and mediates proteolysis of extracellular matrix proteins during cellular invasion [4] . suPAR modulate the functions of integrins (including activating intracellular signals, monocyte chemotaxis, cell adhesion and proliferation) [4,5] . So suPAR contributes to cell adhesion, migration, proliferation inflammation, chemotaxis, proteolysis, immune system activation, tissue remodeling and signal transduction [5,6] .…”
Section: Serum Soluble Urokinase-type Plasminogen Activator Receptor mentioning
confidence: 99%
“…suPAR modulate the functions of integrins (including activating intracellular signals, monocyte chemotaxis, cell adhesion and proliferation) [4,5] . So suPAR contributes to cell adhesion, migration, proliferation inflammation, chemotaxis, proteolysis, immune system activation, tissue remodeling and signal transduction [5,6] . Several studies have identified that suPAR level is a important marker in patients with various diseases and associated with a poorer outcome in a range of non-infectious and infectious diseases [2] .…”
Section: Serum Soluble Urokinase-type Plasminogen Activator Receptor mentioning
confidence: 99%